The role of the level of biochemical markers of inflammation and protective systems of the organism in blood serum and in seminal fluid in patients with chronic prostatitis - V. V. Shuhtin; V. N. Sknar; I. N. Shuhtina; W. Zukow (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2016)
Chronic prostatitis is one of the most common urological diseases. The most socially active groups of the population suffer the most from chronic prostatitis. Most complications of this disease lead to the most undesirable consequences: a decrease in potency, a pain syndrome that complicates the daily activities of patients, dysuria and the possibility of exacerbation of the inflammatory process, which manifests itself in a sharp increase in the exudative reaction, even before the abscess. The article discusses the results of observations of patients with chronic prostatitis in healthy men aged 20-45 years without somatic diseases. Studies were conducted to determine the role of the level of biochemical markers of inflammation of the body's defense systems in blood serum and in semen in patients with chronic prostatitis.